Synergistic Microbial Consortium for Bioenergy Generation from Complex Natural Energy Sources - Victor Bochuan Wang; Joey Kuok Hoong Yam; Song-Lin Chua; Qichun Zhang; Bin Cao; Joachim Loo Say Chye; Liang Yang (The Scientific World Journal)
Microbial species have evolved diverse mechanisms for utilization of complex carbon sources. Proper combination of targeted species can affect bioenergy production from natural waste products. Here, we established a stable microbial consortium with Escherichia coli and Shewanella oneidensis in microbial fuel cells (MFCs) to produce bioenergy from an abundant natural energy source, in the form of the sarcocarp harvested from coconuts. This component is mostly discarded as waste. However, through its usage as a feedstock for MFCs to produce useful energy in this study, the sarcocarp can be utilized meaningfully. The monospecies S. oneidensis system was able to generate bioenergy in a short experimental time frame while the monospecies E. coli system generated significantly less bioenergy. A combination of E. coli and S. oneidensis in the ratio of 1 : 9 (v : v) significantly enhanced the experimental time frame and magnitude of bioenergy generation. The synergistic effect is suggested to arise from E. coli and S. oneidensis utilizing different nutrients as electron donors and effect of flavins secreted by S. oneidensis. Confocal images confirmed the presence of biofilms and point towards their importance in generating bioenergy in MFCs.